PENGARUH KARAKTERISTIK KOMITE AUDIT DAN KINERJA INTELLECTUAL CAPITAL TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL - Masita, Mirza; Yuliandhari, Willy Sri; Muslih, Muhamad (E-Jurnal Akuntansi, 2017)
In the era of globalization, intellectual capital is a concern to academics and practitioners because it can be a tool to determine the value of the company. Intellectual capital is regarded as the hidden value which is located between the book value and market value. This study aimed to analyze the the audit committee characteristics and intellectual capital performance on the disclosure of intellectual capital. Characteristics of the audit committee that is used in this research are size of the audit committee, number of audit committee meetings, and financial expertise of audit committees.The population in this study is a state-owned company went public listed on the Stock Exchange the period 2011-2014. The sample selection technique using purposive sampling and acquired 15 companies that were included with the period of 4 years in order to get 60 samples were observed. This research analyzed the annual reports of companies using content analysis. Methods of data analysis in this study is panel data regression using software Eviews 8.0.The results showed that the variable size of the audit committee, number of audit committee meetings,  financial expertise of audit committees and intellectual capital performance simultaneously significant effect on intellectual capital disclosure while partially intellectual capital performance does no effect on intellectual capital disclosure.
Keywords: Characteristics of the Audit Committee, Intellectual Capital Performance, Intellectual Capital Disclosures